Motivational tools used and job satisfaction of employees in the HDMF Pag-ibig Fund Regional Office, Iloilo City - Alminaza, Romela Mae A.; Ampil, Jethsemae A.; Belgira, Marnelee R.; Malabarbas, Kaneth S.
This paper emphasizes the importance of motivational tools used and job satisfaction of employees in the HDMF (Pag-IBIG Fund) Regional Office, Iloilo City. The motivational tools used by HDMF management and how it is designed are identified. How the employees in the organization perceive job satisfaction and how these motivational tools affected the employees' level of job satisfaction are evaluated. Herzberg Two-Factor theory is discussed and proven to be not applied by the HDMF Management. A further study of the application of Herzberg Theory to other types of organization is recommended.